Trust Memediasi Pengaruh Live Streaming Dan Online Customer Review Terhadap Purchase Decision Produk Skincare Pada Tiktok Shop - Klara Rima Angelia; Robertus Basiya (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The aim of this research is to test trust mediating the influence of live streaming and online customer reviews on purchasing decisions for skincare products at the Tiktok Shop. This type of research is quantitative research. The population of this research is 100 consumers who shop for skincare at the Tiktok Shop. The data analysis technique uses multiple linear regression analysis. The results of this research show that live streaming has a positive and significant effect on trust, online customer reviews have a positive and significant effect on trust, live streaming has a positive and significant effect on purchase decisions, online customer reviews have a positive and significant effect on purchase decisions, trust has a positive and significant effect on purchase decisions, trust mediates the influence of live streaming on purchase decisions, and trust mediates the influence of online customer reviews on purchase decisions.